The rights of victims of illegal investment crimes against confiscated goods - Wayan Santoso (Borobudur Law Review, 2022)
Illegal investment is a very disturbing business crime. The number of victims and the large value of losses make the case of illegal investment getting special attention. The return of losses from the proceeds of crime is actually the right of the victim, but in law enforcement practice, confiscated objects are usually returned to the state, not to the victim as the rightful party. This study will discuss the problems of investment law in business activities, illegal investment in crime terminology and victims' rights to confiscated objects. This research is normative juridical research examining the legal vacuum of confiscation of assets to be returned to the victim. The results show that investment is a business activity protected by law. In its development, there are investment irregularities in the form of illegal investments, namely investments that are not licensed and carried out against the law. Illegal investment in the terminology of crime is not explicitly stated, but this act is punishable by fraud and money laundering. The proceeds of crime are traced and confiscated, but in legal practice, the return is given to the state. In future legal reformulations, it is necessary to stipulate provisions regarding the seizure of assets; therefore, the victims can get their rights.